ChemInform Abstract: MYb(BH4)4 (M: K, Na) from Laboratory X‐Ray Powder Data. Issue 9 (4th March 2014) - Wegner, Wojciech; Jaron, Tomasz; Grochala, Wojciech
Abstract Polycrystalline KYb(BH4)4 and NaYb(BH4)4 are prepared by solid state mechanochemical reactions of 1:3:1 mixtures of YbCl3, LiBH4, and KBH4 or NaBH4, resp.